Stress, anxiety and depression among private higher education student during Movement Control Order (MCO) in Malaysia - Asmadi Abdul Rahman,; Fahmi Zaidi Abdul Razak,; Norillah Abdullah Hassim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A student’s success depends on an emotional stability as well as a calm atmosphere. Stable emotions and well-controlled stress levels will help students to live healthy and succeed in lessons. The emotional stress faced by Malaysian teenagers is alarming, especially among student’s higher education institutions students. If stress cannot be properly treated, the disease is worried to become more serious. Nevertheless, studies that measure the level of stress among religious students are somewhat less. The objective of this research is to examine the level of depression, anxiety and stress among private higher education students in Malaysia. This study uses a quantitative approach to meet the objectives of the study. Respondent were 510 students (366 percent male and 193 female) from one private higher education students in Kuantan who were studying in both diploma and degree level. Participants were selected using a convenience sampling technique and were assessed using questionnaire. To reduce the problem of common method bias in survey research, a number of preventive approaches have been adopted, among them, to convince respondents that this study is for academic purposes only. Findings revealed that the stress level among students were normal during MCO. In terms of stress level, average DASS score was found to be light at 6.8 and as for anxiety were found to be light at 5.7 and average DASS to do score for depression was 5.6 which is normal. This study also proves that students with a religious education background are not exempt from stress.